A Study on Women Empowerment and Entrepreneurial Intention among Small Business of Women Entrepreneurs in the Czech Republic - J. Jose Prabhu (Yayasan Ahmar Cendekia Indonesia, 2020)
Entrepreneurship refers to establishing of a brand-new business to take advantages from brand-new chances. Entrepreneur is the vital element of entrepreneurship and also now women in Czech Republic are additionally effective in this as they have qualities preferable for entrepreneurship advancement. Entrepreneurship is a much ideal profession for women than regular work. Females are thought about an important human resource of the country and every state need to try to utilize them as arbitrators of economic growth and also advancement. Empowerment of women has actually become a vital concern in current times. This write-up manages empowerment of country females via entrepreneurship as well as the benefits entrepreneurship among the small company.